Electrochemical behaviors of uric acid, xanthine, and hypoxanthine at polythiophene-chitosan-modified glassy-carbon electrode - Nhàn, Đặng Thị Thanh; Phong, Nguyễn Hải; Phương, Huỳnh Thị Linh; Thắng, Lê Quốc (Hue University Journal of Science: Natural Science, 2019)
In this study, polythiophene-chitosan-modified glassy-carbon electrodes were used for the simultaneous determination of xanthine, hypoxanthine, and uric acid by the differential pulse anodic stripping voltammetry method. The electrochemical behaviors of the three analytes on the electrode surfaces were studied through the investigation of the influence of pH and the scanning rate. The results show that the number of electrons and protons involved in the electrode process is equal. An irreversible process takes place on the electrode. The electrochemical processes are adsorption-controlled for hypoxanthine and mixed diffusion/adsorption-controlled for xanthine and uric acid.